For a line to be perpendicular all you need is the negative inverse slope.
y=2x-3 has a slope of 2 so the negative inverse would be (-1/2)
So y=(-1/2)x-3 would cross perpendicular at the y axis at -3
2006-11-08 08:48:30
·
answer #1
·
answered by bourqueno77 4
·
1⤊
0⤋
lines are perpendicular if their slopes are adverse reciprocals. y= 2x + 3 slope of the perpendicular line is -(a million/2) y = mx + b 2 = -(a million/2)(-4) + b 2 = 2 + b b = 0 So the equation is y = -(a million/2)x #21) x int is even as y=0 3x = 9 x =3 y int is even as x =0 2y -8 = 0 y = 4 2 factors on the line (3,0) and (0, 4) slope is (4-0) / (0 - 3) = -4/3 y int = 4 from above so y = -(4/3) x + 4
2016-11-28 22:31:51
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
you divide -1 by the slope of your line to find the slope that is perpendicular to your line.
-1divided by 2 is -1/2, so -1/2 is the slope of the line perpendicular to y=2x-3
2006-11-08 08:49:58
·
answer #3
·
answered by tamana 3
·
0⤊
0⤋
Y=mx + b
the slope of the perpendicular line is -1/m...
in this case m=2, so the slope of the perpendicular line is -1/2
2006-11-08 08:49:11
·
answer #4
·
answered by Chris R 1
·
0⤊
0⤋
-1/2
2006-11-08 09:12:52
·
answer #5
·
answered by J 6
·
0⤊
0⤋
the slope of a perpendicular line is the negative reciprocal of the original line.
y=mx+b and y= -(1/m)x+b
So your perpendicular slope would be -1/2
y= (-1/2)x - 3
2006-11-08 08:49:59
·
answer #6
·
answered by swimmerd76 2
·
0⤊
0⤋
its -1/2.
2006-11-08 08:49:10
·
answer #7
·
answered by yljacktt 5
·
0⤊
0⤋
-1/2
the 2 is the slope of the original line, so take the negative of the reciprical
-1/slope
2006-11-08 08:48:40
·
answer #8
·
answered by igot4onit 2
·
0⤊
0⤋
ok.
heard of this rule?
let the gradient of a line be x, and the gradient of the perpendicular line be x'
x*x' = -1.
so the slopeof the perpendicula to this line is -1/2.
Hope this helps=)
apl
2006-11-08 08:49:36
·
answer #9
·
answered by luv_phy 3
·
0⤊
0⤋
m1 - Slope of line one.
m2 - Slope of line two.
For perpendicular lines, m1 * m2 = -1.
Given: y = 2x - 3
→ m1 = 2
m1 * m2 = -1
2 * m2 = -1
m2 = -1/2
Answer: -1/2.
2006-11-08 08:54:54
·
answer #10
·
answered by Brenmore 5
·
0⤊
0⤋